An Algorithm of Decomposing the Trend and Cyclical Components of FDI Inflows: the Case of Ukraine - Bogdan A. Moskalenko; Pavlin Mitev (Financial Markets, Institutions and Risks)
The article summarizes the arguments within the scientific challenge on improving approaches to country investment potential evaluation. The main objective of the research is to systematize the existing statistical methods of decomposing macroeconomic time series into growth (trend) and cyclical components. Systematization of theoretical and methodological materials on solving the problem of decomposing the trend and cyclical components of time data series showed that the use of filtering series of economic dynamics based on the Hodrick-Prescott filter allows identifying long-term growth trends or recessions. The relevance of solving this problem is that the country investment potential evaluation is often based on investigating the impact of foreign direct investment`s determinants in a domestic economy while ignoring cyclical macroeconomic processes within and outside the country, on which those determinants often have not responded yet or reacted late. The methodical tools of the research are carried out in the following logical sequence: systematization of existing statistical methods for trend component decomposing; analysis of data that will be used in the decomposition process and in further country investment potential evaluation; application of the Hodrick-Prescott filter and trend component decomposing in foreign direct investment net inflows dynamics into the economy of Ukraine. The Research methods combine in following dimensions: comparative analysis, regression analysis and univariate methodology of time series decomposing. The period from 1999 to 2019 was chosen as the research period. The object of the research is foreign direct investment net inflows into the economy of Ukraine, as they are the determining element within the country investment potential evaluation process. The article presents the results of empirical analysis, which showed that the decomposing a trend and cyclical components of foreign direct investment inflows can improve the quality of investment potential evaluation, considering the impact of current economic cycle phase. The results of the research can be useful for a more accurate investment potential evaluation on the macroeconomic level and forecasting foreign direct investment inflows for the following time periods.